2007
DOI: 10.3844/ajessp.2007.30.36
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Issues in Jordan, Solutions and Recommendations

Abstract: Jordan's natural resources are limited to support population in a sustainable manner. However, its environment is exposed to a number of threats. In order to best explain Jordan's environmental difficulties, it would be prudent to focus individually on each of these major concerns: water shortages, agriculture/land and air pollution. This study focuses on the environmental problems in Jordan and has addressed the process of reversing environmental decline. A true foundation of environmental protection requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Resource overexploitation: Overexploitation of water resources in FC countries, such as overuse of aquifers could lead to water quality impacts (Hadadin and Tarawneh 2007).…”
Section: Constraints To Water Reallocationmentioning
confidence: 99%
“…Resource overexploitation: Overexploitation of water resources in FC countries, such as overuse of aquifers could lead to water quality impacts (Hadadin and Tarawneh 2007).…”
Section: Constraints To Water Reallocationmentioning
confidence: 99%
“…4a). These are described qualitatively by a model representing five layers where the layer resistivity relationship is ρ 1 > ρ 2 < ρ 3 < ρ 4 < ρ 5 ; the results were of the HKK type (Table 1). Based on borehole information and field observations, the conceptual layered-earth model that best fits a Type I curve is composed of (i) a topsoil layer; (ii) a low-resistivity layer representing the surficial deposit unit; (iii) a layer of marl, chalk and chalky marl of the MCM formation with low resistivities; (iv) a moderately low-resistivity layer, representing limestone and phosphate with chalk and chalky marl of the AHP formation, and (v) a layer of limestone comprising the aquifer.…”
Section: Analysis Of Ves Curvesmentioning
confidence: 99%
“…Moreover, the available renewable water resources are declining drastically because of high population growth, rapid agricultural and industrial development and the rapid influx of refugees caused by regional political instability. Several previous studies relating to the water sector in Jordan have generally concluded that there is a need to address future impacts of water shortages through resource planning and development [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Surface water from the Yarmouk River, peace treaty water and non conventional water resources including desalinization and groundwater from non renewable aquifers are the major components forming the additional water resources [1] . Figure 1 shows the distribution of water resources in Jordan in million cubic meters (Mm 3 ) and the percentage of each resource for the year 2005 as estimated by the Ministry of Water and Irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the available renewable water resources are dropping drastically to an annual figure of 160 m 3 /capita in recent years compared to 3600 m 3 /capita for the year 1946. The dramatic decrease in both renewable and non-renewable resources is due to the steep population growth, rapid agricultural and industrial developments and the sudden influx of refugees due to political instability in the region [3] . In the year 2001, the country's total water demand was in the range of 1350 Mm 3 , of which, only 774 Mm 3 was supplied due to water shortages resulting from drought conditions.…”
Section: Introductionmentioning
confidence: 99%